2014
DOI: 10.3390/diseases2040301
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter-pylori Negative Gastritis in Children—A New Clinical Enigma

Abstract: Abstract:The decrease in the prevalence of Helicobacter pylori (Hp) infection in children in the world gave rise to a new pathological finding termed as Hp-negative gastritis. Unfortunately, the term "Hp-negative gastritis" has not been identified as a pathological process and has the status of a "second cousin"; in most publications it was never mentioned as a subject to be dealt with, but was "left over" data that was never the topic of the manuscripts' discussions. Only recently has the topic captured the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“… 13 , 14 This is significantly higher than that reported in children in the USA (3%–7%). 15 We also found a higher prevalence (60.7%) of gastritis without H. pylori than observed previously in children from Turkey (40%), Mexico (44%), and the USA (50%). 7 9 Studies in adults have shown a much lower proportion of Hp− gastritis.…”
Section: Discussionsupporting
confidence: 62%
“… 13 , 14 This is significantly higher than that reported in children in the USA (3%–7%). 15 We also found a higher prevalence (60.7%) of gastritis without H. pylori than observed previously in children from Turkey (40%), Mexico (44%), and the USA (50%). 7 9 Studies in adults have shown a much lower proportion of Hp− gastritis.…”
Section: Discussionsupporting
confidence: 62%
“…The prevalence of H pylori ‐negative gastritis in pediatric EGDs has previously been reported to be between 37% and 94%. Available studies have usually included all gastritides and/or gastroparesis, not just chronic forms as is the case in our study (3,4,21,22). The focus of previous studies has been mainly on H pylori ‐positive gastritides with report of H pylori‐negative findings (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although still widespread in developing countries, H pylori is becoming rare in developed countries. Simultaneously, the finding of H pylorinegative chronic gastritis (HPNCG) appears to be increasing (3,4).…”
mentioning
confidence: 99%